PENGEMBANGAN GAME JEGOG BERBASIS ANDROID - I Gede Wija Antara; I Gede Mahendra Darmawiguna; I Made Gede Sunarya (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2014)
Gamelan Jegog is one of thetraditional instrument which originally comesfrom Bali. Each Jegog’s instrument consists ofeight piece of bamboo with each piece is called as"bilah". Jegog is played with two "panggul".“Panggul” is a tool used for hitting theinstrument and is usually made of wood orrubber. Game Jegog berbasis Android was anapplication that adapts Jegog into a game thatrun on the Android platform. This researchaimed at designing and implementing Jegogbased Android Game.Game Jegog Berbasis Android wasdeveloped by the Software Development LifeCycle (SDLC) in the form of sequential linear orwaterfall model. The main feature of thisapplication was Jegog game (Game Mode) toattain the highest score . There were also otherfeatures such as playing Jegog with melody(Learn Mode) and playing Jegog freely (FreeMode) .The results of this research were thedesign and the implementation of Game Jegogberbasis Android . The game was designedthrough UML (Unified Modeling Language). Itwas implemented in Java programming languageby using the Eclipse editor and ADT (AndroidDevelopment Tools) plug – ins. It also usedAndEngine as additional library. The entirefunctional requirements had been successfullyimplemented in accordance with the design.